Konversi Limbah Biomassa Tandan Kosong Sawit menjadi Energi Panas - Erdiwansyah; Muhtadin; Asri Gani; Muhammad Faisal; Muhammad Nizar; Yeggi Darnas (Jurnal Serambi Engineering, 2024)
Biomass waste from palm oil mill processing in Indonesia, especially on the island of Sumatra one of which is Aceh Province, is currently quite abundant and has not been managed optimally. This biomass waste can be converted into solid energy, which can be used as energy for biomass power plants. The aim of this research is specifically to convert biomass waste into solid energy. This research applies Simultaneous compression with heating as a fuel production method. The biomass waste used as solid fuel production material is empty palm oil bunches. The results of the fuel production process based on palm oil biomass waste show that the energy value reaches 26.80 MJ/kg. The carbon content in the produced fuel reaches 47.56%, with a low ash content of 6.70%. Calculations of the density of biomass-based fuel before and after production show an average of 1.42 grams/cm3. The results of tests carried out on fuel produced using palm oil biomass waste show high energy potential that can be used to reduce dependence on the use of coal.